2007
DOI: 10.1016/j.jinf.2007.04.354
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine coverage rates and perceptions on vaccination in South Korea

Abstract: Doctor's recommendation was the most important factor in encouraging people to be vaccinated against influenza. Doctors should be geared up with precise information and actively encourage high risk population in order to increase vaccination coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
92
4
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 26 publications
13
92
4
8
Order By: Relevance
“…In the Republic of Korea (ROK), the influenza vaccine coverage rate was an estimated 80% in elderly individuals, and pneumococcal vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPV23) was adopted as the national immunization program for elderly individuals (Ն65 years of age) in May 2013 (8,9). This study evaluated the effectiveness of influenza and pneumococcal vaccination alone or in combination to prevent pneumonia and hospitalization following influenza-like illness (ILI).…”
mentioning
confidence: 99%
“…In the Republic of Korea (ROK), the influenza vaccine coverage rate was an estimated 80% in elderly individuals, and pneumococcal vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPV23) was adopted as the national immunization program for elderly individuals (Ն65 years of age) in May 2013 (8,9). This study evaluated the effectiveness of influenza and pneumococcal vaccination alone or in combination to prevent pneumonia and hospitalization following influenza-like illness (ILI).…”
mentioning
confidence: 99%
“…Only 33 (18.9%) of the subjects in this study were influenza vaccine na€ ıve, as the influenza vaccine coverage rates in South Korea had been quite high (84.8%) in the risk group. 25 In conclusion, influenza vaccines in this study provided an adequate 1-year immunity to influenza H1N1 and H3N2 without differences between split and subunit vaccines in children and adolescents. The immunogenicity at one month after vaccination influenced further serological influenza infections.…”
Section: Discussionmentioning
confidence: 56%
“…17 Several authors found that a high proportion of non-vaccinated high-risk persons thought they did not qualify for the vaccination and reported having good health. 18,19 Age-based strategies have a series of advantages and disadvantages. The advantages of the age-based strategy include the possible reduction in health care expenditure and in the annual work-related economic burden of influenza morbidity.…”
Section: Discussionmentioning
confidence: 99%